Renal Artery Stenosis- First Renal Stenting in BSMMU, a case report - Ahsan, SA; Awal, A; Bari, AS; Haque, MA; Shrestha, MP; Salman, M (University Heart Journal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Fifty years old diabetic houswife presented with poorly controlled hypertension, shortness of breath and intermittent claudication of lower limbs. She was mildly anaemic and had absent pulses in lower limbs and renal bruit and crepitations in lungs bases. Her Hb% was 9.1 gm/dl and S. creatinine was 2.5 mg/dl, Chest X-ray showed cardiomegaly with pulmonary oedema and echocardiogram showed mild systolic dysfunction (EF- 48%). Coronary, renal and peripheral angiography revealed severe coronary artery disease, 95% stenosis in left renal artery and 40% stenosis in right renal artery, significant stenosis in both femoral arteries. Patient underwent left renal angioplasty with uneventful procedure. Her blood pressure and serum creatinine comes down to normal. University Heart Journal Vol.4(1) January 2008